The Use of Round Table Technique to Enhance Writing Skills of Discussion Text for Senior High School Students - Niken Dyah Ayuningtiyas (Retain: Journal of Research in English Language Teaching, 2026)
Writing is a significant element in language learning, particularly English that uses different kinds of text, such as discussion text. This research is intended to examine the effectiveness of Round Table Technique (RTT) in enhancing students’ writing skill on discussion text. Method: This quasi-experimental quantitative study was conducted in two groups, 65 high school students were divided among experimental (N=33) and Control (N=32). The data were obtained from the pre-test and post-test used adapted IELTS Academic Writing Sample Test, and analyzed in the Mann-Whitney U Test. The findings indicated that RTT elicited a medium effect (0.38) for enhancing students ' writing performance and experimental group outperformed their control counterparts (M=5.76; M=1.09). This research demonstrates that round table technique effectively enhances the skill to write a discussion text by means of collaborative learning which encourages active participation, and critical thinking since students could argue. These results have implications for the importance of utilizing the teachers' use of structured discussion and facilitation skills to promote inclusive learning and enhance students ‘writing performances as well as academic achievement.